Upaya Meningkatkan Proses Pembelajaran Tematik Terpadu Dengan Menggunakan Model Problem Based Learning : Indonesia - Nofita Tryana Tryana; Anggi Fitri; Syahri Ramadhan; Zalisman; Ayu Purnamasari S; Evi Rahayu; Nikmah (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2021)
This study aims to determine the improvement of the thematic integrated learning process with the problem-based learning model. The method used is Classroom Action Research. The research was carried out in two cycles, each cycle consisting of two meetings, with stages, namely: planning/preparing for action, implementing the action, observing, and reflecting. Data collection techniques using observation techniques, the use of questionnaires, and documentation. Based on the research results, it is known that there is an increase in the integrated thematic learning process from before the action, Cycle I, and Cycle II. In the first cycle of student learning activities of 741 an increase in the second cycle of 84%. The value of the student activity questionnaire in the first cycle was 3.7, an increase in the second cycle was 4.2. Thus, the use of problem-based learning models can improve the integrated thematic learning process in class V SD Negeri 131 Pekanbaru.